Decolonization in health professions education: reflections on teaching through a transgressive pedagogy - Rodney, Ruth (Canadian Medical Education Journal, 2016)
Background: Canadian health educators travel to the global south to provide expertise in health education. Considering the history of relations between the north and south, educators and healthcare providers from Canada should critically examine their practices and consider non-colonizing ways to relate to their Southern colleagues. Methods: Using her experience as a teacher with the Toronto Addis Ababa Academic Collaboration in Nursing, the author explored issues of identity and representation as a registered nurse and PhD candidate teaching in Ethiopia. Transgressive pedagogy was used to question how her personal, professional, and institutional identities impacted her role as a teacher. Results: Thinking and acting transgressively can decrease colonizing relations by acknowledging boundaries and limitations within present ideas of teaching and global health work and help moving beyond them. The act of being transgressive begins with a deeper understanding and consciousness of who we are as people and as educators. Conclusion: Working responsibly in the global south means being critical about historical relations and transparent about one’s own history and desires for teaching abroad.